The Impact Of Divestitures (Spin-offs And Sell-offs) Announcements On The Share Price Performance Of Parent’s Companies: South African Listed Companies - Oyedotun, Ibukun (Department of Finance and Tax, 2020)
This thesis is based on the empirical examination of the impact of divestiture announcements, with a focus on spin-off and sell-off transactions, on the share performance of parent companies listed on the Johannesburg Stock Exchange (JSE) in South Africa. The sample of the study for spin-off consisted of 36 companies while that of sell-off transactions consisted of 41 companies listed on JSE for deals that were announced and concluded from 2006 to 2016. The cumulative average abnormal returns for the parent companies were calculated using the event study methodology over the entire event window. Abnormal returns were calculated using the two-factor APT model approach. The cumulative average abnormal returns significance was tested using the t-test. Thereafter, the average abnormal returns and cumulative average abnormal returns were compared over the event window for the pre and post announcement period. A comparison was also made between spin-off and sell-off transactions over the entire event window (-30, +30). Three key results were established, the first being that, spin-off transactions generate positive abnormal returns while sell-off transaction generate negative abnormal returns. Second, it is clear that there were significant positive cumulative average abnormal returns for postannouncement returns for spin-off transactions while the post-announcement returns for sell-off transactions generated a negative cumulative average abnormal returns. Thirdly, I compared the two form of divestiture (spin-off and sell-off transactions) and discovered that there appears to be significant evidence that the CAAR for spin-off transactions are higher than the CAAR for sell-off transactions.